Interactions between commercial fishing vessels and a pelagic seabird in the southern Mediterranean Sea - Cianchetti-Benedetti, Marco; Dell´Omo, G.; Russo, T.; Catoni, C.; Quillfeldt, Petra; Justus Liebig University Giessen (My University, 2018)
BACKGROUND: Fishing activities can influence foraging behaviour of many seabird species worldwide. Seabirds are attracted by fishing vessels which can facilitate access to demersal fish as a novel food resource that otherwise would be unavailable. On the other hand, intense fishing activities cause depletion of fish stocks with a reduction of natural prey available for seabirds. Moreover, fisheries discards can have lower nutritional value than natural prey. However, the importance of fisheries discard for seabirds and the possible implications on their foraging ecology is still poorly understood. In this study, we analysed the interactions of Scopoli´s shearwaters (Calonectris diomedea) during their foraging trips with fishing vessels. We combined the GPS and accelerometer data of shearwaters with the GPS data gathered during the same period from fishing vessels. Accelerometers allowed us to identify the main behaviours of birds.RESULTS: The presence of fishing vessels significantly affected the individual behaviour of Scopoli´s shearwaters. Birds increased the time spent sitting on the water within 1.28 +/- 0.13 km of fishing vessels likely feeding or waiting for discards. Approaches towards vessels within the interaction distance were therefore classified as an interaction and were recorded in about 40% of individuals. Birds interacting with fisheries had longer flight time during their foraging trips and covered longer distances to reach more distant foraging areas compared with individuals not approaching vessels.CONCLUSIONS: Our results suggested that fisheries discard consumption might not be a profitable source of food for Scopoli´s shearwaters. Despite the high density of fishing vessels in the home range of Scopoli´s shearwater, most individuals did not interact with them. Accordingly, scavenging individuals showed a lower foraging efficiency than their conspecifics. Intraspecific competition for foraging areas might play an important role for the foraging decision of birds to consume fisheries discards.
Keywords: fisheries discards; fishing vessel-seabird interactions; foraging ecology; Scopoli´s shearwater (Calonectris diomedea); GPS; ddc:570